Risk Factors Analysis of Premature Canities in Medical Students of Universitas Sumatera Utara Class 2016-2018 - Eka Zhaki Safira Lubis; Jusuf, Nelva Karmila (Sumatera Medical Journal, 2020)
Abstract. Background. Premature canities is a terminology to describe a premature graying of hair before the age of 25 in Asians.The ethiopathogenesis of premature canities is still not fully understood, but there are risk factors associated to premature canities such as gender, family history, obesity, smoking, alcohol consumption, other disease, micronutrients deficiencies. Aims: to evaluate risk factors that influence the incidence of premature canities in medical students of University of Sumatera Utara class 2016-2018. Methods: This research is an analytic research with the number of subjects are 80 respondents using bivariate and multivariate analysis using logistic regression test. Results: of the 80 respondents, 57 respondents (71,2%) had premature canities. Based on bivariate analysis, it was obtained p value ≤ 0,05 for family history and stress, Based on multiavariate analysis, it was obtained p value ≤ 0,05 for family history (p value = 0,000), which means family history is the most dominants factors for premature canities. Conclusion: there is a correlation between premature canities and family history and stress and Family history is the most dominant risk factors that associated to premature canities in medical students of University of Sumatera Utara class 2016-2018.